PRAKTIK KEHIDUPAN EKONOMI PEKERJA WANITA PADA PABRIK ROKOK GUDANG GARAM MERAH (APACHE) DALAM TEORI GENDER - Wahibatul Maghfuroh (Fakultas Agama Islam UNISMA, 2019)
Women work because of the heavy family burden, and the lower economic demands cause a female worker to work at the Gudang Garam Merah company known as the